2018
DOI: 10.24114/jpb.v7i2.10625
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Metakognitif, Kemampuan Berpikir Kritis, Bimbingan Orang Tua dan Guru tentang Kesehatan Reproduksi dengan Persepsi Perilaku Seksual Siswa SMA Se-Kota Medan

Abstract: This research intended to identify: (1) Student metacognition about reproduction health, (2) student critical thinking skill about reproduction health; (3) Student perception of sexual behaviour, (4) Parents’ and teachers’ guidance about reproduction health, (5) Teachers’ guidance about reproduction health, (6) The correlation among metacognitive, critical thinking, parents’ and teachers’ guidance about reproduction health into perception of sexual behaviour. This correlation study was conducted at Senior high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Upaya meningkatkan kualitas pembelajaran tentang Sistem Reproduksi telah dilakukan melalui penelitian quasy experiment dengan menerapkan model kooperatif think pare share menggunakan video (Sagala & Djulia, 2016), serta hubungan antara metakognisi kesehatan reproduksi dengan persepsi perilaku seksual siswa (Sapitri, Sipahutar, Djulia, 2014). Namun masih minim penelitian yang membangun sikap dan respons positif siswa terhadap perkembangan pubertas.…”
Section: Pendahuluanunclassified
“…Upaya meningkatkan kualitas pembelajaran tentang Sistem Reproduksi telah dilakukan melalui penelitian quasy experiment dengan menerapkan model kooperatif think pare share menggunakan video (Sagala & Djulia, 2016), serta hubungan antara metakognisi kesehatan reproduksi dengan persepsi perilaku seksual siswa (Sapitri, Sipahutar, Djulia, 2014). Namun masih minim penelitian yang membangun sikap dan respons positif siswa terhadap perkembangan pubertas.…”
Section: Pendahuluanunclassified
“…Some research results regarding the relationship between environmental cognitive and environmental caring attitudes include: Sirait (2015) found that there is a significant relationship between students' cognitive level and environmental loving behavior, meaning that the higher the environmental cognitive value, the higher the environmental loving behavior value student. On the other hand, the lower the cognitive value of the environment, the lower the students' environmental loving behavior will be.…”
Section: Introductionmentioning
confidence: 99%